Fractionation and characterization of oil palm (Elaeis guineensis) as treated by supercritical water - Varman, M.; Miyafuji, H.; Saka, S. (2010)
In order to investigate a potential for the efficient utilization of oil palm (Elaeis guineensis), supercritical water treatment (380ºC/100MPa/8s) has been applied to fractionate into water-soluble portion and water-insoluble portion composing of methanol-soluble portion and methanol-insoluble residue for various parts of oil palm such as trunk, frond, mesocarp fibers, shell, empty fruit bunch (EFB) and kernel cake. These fractionated products were then characterized analytically, in which the water-soluble and methanol-soluble portions were determined to be mainly composed of carbohydrate-derived products and lignin-derived products, respectively. Besides, the methanol-insoluble residue was mainly composed of lignin more than 84wt%, and the phenolic hydroxyl contents determined by aminolysis method was higher than the untreated oil palm sample. In addition, an alkaline nitrobenzene oxidation analysis indicated that, the methanol-insoluble residue was less in oxidation products. These lines of findings implicate that the water-soluble portion could be utilized for organic acid production, whereas the methanol-soluble portion and its insoluble residue for phenolic chemical production.